Headache and facial pain - Newman, Lawrence C., M.D.; Levin, Morris, 1955- (New York : Oxford University Press, 2009)
This resource presents a representative set of 33'mini-cases' of headache and facial pain, and is divided into three sections that cover the typical ground for head/face pain consultation: (1) Diagnostic Questions, (2) Treatment Considerations, and (3) Prognostic, Social and Legal Issues. Recommendations are based on the most current evidence available, and diagnostic thinking is presented along the lines of the International Classification of Headache Disorders, second edition (ICHD-II).
Erratum slip inserted.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Headache -- Case studies; Facial pain -- Case studies